2019
DOI: 10.3122/jabfm.2019.04.190064
|View full text |Cite
|
Sign up to set email alerts
|

Declining Endoscopic Care by Family Physicians in Both Rural and Urban Areas

Abstract: Using data from 2014 through 2016, we demonstrated a decline in the percentage of family physicians providing endoscopic services in both rural and urban areas. Our findings suggest that forces in the health care system may be influencing the reduction in scope, rather than specific geographic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Family physicians may deliver endoscopy services, but prior research showed that fewer than 5% actually do so and that the percentages declined between 2014 and 2016. 26 In a study based on 2006 and 2007 Medicare Beneficiary Survey and Medicare claims, residents of metropolitan areas whose usual physician was a general internist had higher odds of colorectal screening than those whose usual physician was a family physician. 27 However, there was no association between physician specialty and colorectal screening among non-metropolitan residents.…”
Section: Discussionmentioning
confidence: 99%
“…Family physicians may deliver endoscopy services, but prior research showed that fewer than 5% actually do so and that the percentages declined between 2014 and 2016. 26 In a study based on 2006 and 2007 Medicare Beneficiary Survey and Medicare claims, residents of metropolitan areas whose usual physician was a general internist had higher odds of colorectal screening than those whose usual physician was a family physician. 27 However, there was no association between physician specialty and colorectal screening among non-metropolitan residents.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer of us are delivering babies, inpatient rounding, or spending time in the operating room. [6][7][8] This is not to disparage an outpatient-only practice nor elevate a full-spectrum one; we deserve the career we have been trained to perform. As the health care landscape shifts, and advanced skills and procedures are squeezed out of family medicine, it's time to ask: Do we want to let go of this part of our practice?…”
Section: To the Editormentioning
confidence: 99%
“…33,34 As the subject-matter expert on patients themselves, it is perhaps concerning to witness decreases in many dimensions of comprehensiveness among family physicians, including declines in provision of inpatient, obstetric, pediatric and procedural care. [35][36][37][38] Educators revising residency guidelines should be aware that comprehensiveness, like continuity, has been recently demonstrated as measurable at the physician level and associated with lower medical costs and hospitalizations. 39 Also important is its association with lower levels of burnout, 40 and the finding that intended scope of practice among family medicine graduates is broader than actual practice.…”
Section: Comprehensivenessmentioning
confidence: 99%